Platón : el filósofo romántico que condenó a los poetas = Platón : the romantic philosopher who condemned poets (2017)
This article reconstructs the basic motive for Platon's censure of certain poetry in his famous book, the Republic, based on the reasoning of Socrates on the ideal basis of a well censures certain poetry in his famous book the Republic, based on the reasoning offered by Socrates on the ideal basis of a well-constituted polis. This allows us to observe the ambivalence of the censure that Platon applies to poets, in particular to Homer and Hesiodorus. To Homer and Hesiod in particular, for it expresses a legitimate concern in a rather problematic way. However, in a rather problematic way, since it can lead to the execution of abuses that are in turn condemnable. This reconstruction and critique of Platon is the object of this paper